2019
DOI: 10.1167/iovs.19-26914
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Tear Fluid Nociception-Associated Factors, Corneal Dendritic Cell Density, and Vitamin D Levels in Evaporative Dry Eye

Abstract: Citation: Khamar P, Nair AP, Shetty R, et al. Dysregulated tear fluid nociception-associated factors, corneal dendritic cell density, and vitamin D levels in evaporative dry eye. Invest Ophthalmol Vis Sci. 2019;60:2532-2542. https://doi.org/10.1167 PURPOSE. The purpose of this study was to study the status and association among tear-soluble factors, corneal dendritic cell density, vitamin D, and signs and symptoms in dry eye disease (DED). METHODS.A total of 33 control subjects and 47 evaporative dry eye pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 76 publications
2
84
1
Order By: Relevance
“…Although a discordance in the association between reduced serum vitamin D levels and DED signs and symptoms was reported, 29,30,46 we had shown that the tear film levels rather than serum vitamin D levels exhibited stronger association with DED signs and symptoms. 9 To further the concept of investigating the local status of vitamin D homeostasis, we investigated the levels of VDR in patients with DED. VDR mediates the cellular response induced by vitamin D and absence of VDR increased basal level of inflammation, rendering cells more susceptible to stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a discordance in the association between reduced serum vitamin D levels and DED signs and symptoms was reported, 29,30,46 we had shown that the tear film levels rather than serum vitamin D levels exhibited stronger association with DED signs and symptoms. 9 To further the concept of investigating the local status of vitamin D homeostasis, we investigated the levels of VDR in patients with DED. VDR mediates the cellular response induced by vitamin D and absence of VDR increased basal level of inflammation, rendering cells more susceptible to stress.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 A number of studies report the association of vitamin D levels, including tear vitamin D and DED along with the restoration of tear film osmolarity following vitamin D supplementation. 9,[26][27][28] However, there has also been contradicting studies regarding the relationship between serum vitamin D levels and DED signs and symptoms. 29,30 These studies suggest an unexplored possibility of dysregulated VDR expression or function, in addition to lower vitamin D levels, in DED.…”
Section: How Might This Change Clinical Pharmacol-ogy or Translationamentioning
confidence: 99%
“…They found that decreased serum vitamin D was significantly associated with higher levels of inflammatory interleukin IL-17A/F, interferon-γ, monocyte chemotactic protein 1, intercellular adhesion molecule 1, IL-4, IL-10, and decreased levels of antinflammatory IL-2 in tears of dry eye patients in comparison to healthy controls [241]. Altered tear fluid soluble factors with potential to modulate nociception exhibited a distinct association with the ocular surface discomfort status [242]. Vitamin D deficiency was found to be associated with neuralgia and chronic pain.…”
Section: Vitamins D and Amentioning
confidence: 99%
“…In a case report it was observed that a vitamin D-deficient patient with corneal neuralgia had relief from burning sensation and pain by vitamin D supplementation, 1,000 IU/day, while topical therapies and lubricants were not effective [243]. It is thus probable that low vitamin D could contribute to the severity of ocular surface symptoms either by directly influencing nociceptive mechanisms or by affecting the presence of inflammatory cytokines [235,236,241,242]. Khamar et al, reported the dysregulation of tear fluid nociception-associated factors, corneal dendritic cell density, and vitamin D levels in dry eye patients.…”
Section: Vitamins D and Amentioning
confidence: 99%
“…Before storage at -80 °C, the tear migration length (a marker for tear volume) was recorded. Tear uid was extracted from the Schirmer strip by agitating small cut pieces of these strips in 60 µL PBS, Tween20 0.5% and cOmplete™ Protease Inhibitor Cocktail (Roche, Basel, Switzerland) at 4 °C for 1.5 hours (16,17). Tear uid was then eluted by centrifugation and stored at -80 °C until further use.…”
Section: Tear Uid Collection and Biochemical Analysesmentioning
confidence: 99%